Realisasi Pelaksanaan Fatwa Mui No. 5 Tahun 2010 Tentang Arah Kiblat di Masjid Kecamatan Medan Tembung - Roki, Ahmadin Amri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article explains that the direction of the Qibla is very important in carrying out worship for Muslims. The scholars agree that people who can see the Kaaba directly must face the Kaaba building ('ainul Kaaba). The Indonesian Ulema Council (MUI) has issued a Fatwa on the direction of the Qibla, namely MUI Fatwa No. 5 of 2010. In this study, the implementation of MUI Fatwa No. 5 of 2010 was realized in Medan Tembung District. To obtain answers to these questions, this study is directed at library research and qualitative field research based on empirical legal research. The data used are mostly secondary data, such as primary legal materials in the form of MUI Fatwas, secondary legal materials in the form of research results, books such as the book Ilmu Falak, Tafsir Ayat-Ayat Hukum, and lecture materials related to the title of this thesis. In addition, the author also conducted interviews. MUI Fatwa No. 5 of 2010 concerning the direction of the Qibla was issued after the stipulation of MUI Fatwa No. 3 of 2010 which was also concerning the direction of the Qibla. The method of measuring the direction of the Qibla of mosques in Medan Tembung District is generally by using a tool, namely a compass. This is proven by the confession of the mosque nazir whom the author interviewed. Then MUI Fatwa No. 5 of 2010 concerning the direction of the Qibla has not been realized in Medan Tembung District. This is due to two things. First, there are 13 mosque nazirs who do not know about this Fatwa. Second, there has been no re-measurement of the direction of the Qibla for 15 mosques in Medan Tembung District.